Penguatan Literasi Keagamaan Mahasiswa Melalui Kajian Kitab Riyadhus Shalihin dalam Program Pengajian Mingguan Mahasiswa Universitas Tazkia - Abdul Mughni (Tamkin Jurnal Pemberdayaan Tazkia, 2026)
This community service program aims to strengthen students' religious literacy through a weekly Islamic study (pengajian) held at the Tazkia Mosque (Andalusia Islamic Center), Tazkia University, Sentul City, Bogor. The program presents a thematic study (bedah kitab) of Riyadhus Shalihin, a classical hadith compilation authored by Imam an-Nawawi that discusses Islamic ethics (akhlak) and etiquette (adab), delivered directly by Ustadz Abdul Mughni. Using an action research approach, the activity was designed, implemented, observed, and reflected upon in a cyclical manner to continuously improve its quality. The study was conducted in a face-to-face halaqah format, in which participants sat together on the mosque carpet to listen to the explanation of hadith, ask questions, and discuss its relevance to daily student life. The results indicate that this weekly study contributes to strengthening students' understanding of Islamic ethics, encourages consistent religious practice, and builds a learning community centered on the mosque as a spiritual, intellectual, and social space. This program is expected to serve as a sustainable model of character education that can be replicated by other study programs or campus mosques.